Methodological Considerations in “Associated Factors for Erectile Dysfunction in Patients with Coronary Artery Disease”: Letter to the Editor - Kamyab Shahrivar (Iranian Journal of Medical Sciences)
I recently have read with great interest an article by Ali Hamidi Madani and colleagues, entitled “Associated Factors for Erectile Dysfunction Occurrence in Patients with Coronary Artery Disease: A Cross-sectional Study”, which was published in your esteemed journal (IJMS Vol 50, No. 1, January 2025).